Assessment of the usefulness of silicone plaster application on a postoperative scar in women after mastectomy because of breast malignancy: a preliminary report - Lipińska, Anna; Terek-Derszniak, Małgorzata; Lipińska-Stańczak, Magdalena; Żurawski, Łukasz; Żurawska, Anna; Ridan, Tomasz; Macek, Paweł; Śliwiński, Zbigniew (Medical Studies/Studia Medyczne, 2017)
Introduction: In the natural process of wound healing a scar is formed, which by its build, colour, and function does not resemble healthy tissue. This concerns not only the appearance of the outer integument, but above all, the deeper layers, which are also subject to the process of scarring. In some cases, a disorder of the decomposition and synthesis of collagen takes place and then hypertrophied scars and colloids are formed. Therefore, in physiotherapeutic practice, a scar should be seen in the three-dimensional aspect. Oncology patients can have so-called silicone dressings applied in the healing process of hypertrophied scars and colloids. The therapy using plasters with silicone gel is safe and non-invasive. Aim of the research: To assess the impact of silicone plasters on postoperative scars in the rehabilitation of women after mastectomy. Material and methods : The study, in which women after mastectomy took part, was performed in the Holycross Cancer Centre in Kielce. The assessment of a postoperative scar was based on the Patient and Observer Scar Assessment Scale (POSAS). Results and conclusions: Silicone dressings applied on a postoperative scar influenced its flexibility, colour, and size. The achieved results are satisfactory, and the applied method is effective and promising. However, the methods used to assess the scar, which are commonly recommended but not quite objective, raise some reservations and doubts among the authors.